2020
DOI: 10.2147/cmar.s232994
|View full text |Cite
|
Sign up to set email alerts
|

<p>Siva 1 Inhibits Cervical Cancer Progression and Its Clinical Prognosis Significance</p>

Abstract: Background: Cervical cancer is the second most common female malignancies. But the exact etiology of cervical cancer is still under investigation. Recent observations revealed that the loss expression of Siva 1 was related to several different types of tumors. It could play an indispensable role in both exogenous and endogenous apoptotic signaling pathways. Nevertheless, the relationship between Siva 1 expression and cervical cancer progression has not yet been fully clarified. This study aimed to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…We found that TP53 activation of the target genes is substantially different among the four profiled regions of the tumor. The negative correlation of TP53 and SIVA1 in both normal tissue and the primary tumor “A” ( Figure S2a ), suggests that increased expression of SIVA1 is reported to inhibit cervical cancer progression [ 106 ] (and hopefully also the progression of prostate cancer) may be achieved by down-regulating TP53. This possibility is based on our “see-saw” model [ 107 ] indicating that similar effects of the increase of one gene expression can be obtained either by up-regulating another gene with a similar coordination profile (the ordered set of Pearson correlation coefficients between the expression levels of that gene with each other gene) or by down-regulating one with opposite coordination.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TP53 activation of the target genes is substantially different among the four profiled regions of the tumor. The negative correlation of TP53 and SIVA1 in both normal tissue and the primary tumor “A” ( Figure S2a ), suggests that increased expression of SIVA1 is reported to inhibit cervical cancer progression [ 106 ] (and hopefully also the progression of prostate cancer) may be achieved by down-regulating TP53. This possibility is based on our “see-saw” model [ 107 ] indicating that similar effects of the increase of one gene expression can be obtained either by up-regulating another gene with a similar coordination profile (the ordered set of Pearson correlation coefficients between the expression levels of that gene with each other gene) or by down-regulating one with opposite coordination.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Siva-1 is downregulated in colorectal cancer and breast cancer (27)(28)(29), but as an important regulator of apoptosis and metastasis, Siva-1 is also highly expressed and facilitates tumorigenesis in a number of malignant tumors, including ovarian cancer (30), osteosarcoma (18), non-small cell lung cancer (17) and gastric cancer (29). Although Siva-1 was initially identified as a promoter of apoptosis (7), the underlying molecular mechanism requires further investigation. The results of the present study indicated that Siva-1 overexpression inhibited apoptosis and enhanced multidrug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…no. oP-0002; epiGentek Group, inc.), 1x10 7 cells were transferred to a 1.5-ml microcentrifuge tube and centrifuged at 500 x g at 4˚C for 3 min to harvest the cell pellet. ice-cold cytoplasmic extraction reagent was added, and the microcentrifuge tubes were left to incubate on ice for 1 min.…”
Section: Measurement Of Dox Pump Rate Via Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond its role in apoptosis, SIVA-1 also regulates other cellular processes, such as cellular migration ( Li et al, 2011 ; Ma et al, 2017 ), autophagy ( Van Nostrand et al, 2015 ), and proliferation ( Ma et al, 2017 ; Liu et al, 2020 ). In cancer studies SIVA-1 has been found to have a role as pro- or anti-malignant factor, depending on cellular context ( Vachtenheim et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%